Moisture Sorption Isotherms of Osmo-Convectively Dried Aonla Fruit - Alam, Md. Shafiq; Singh, Amarjit (Journal of Agricultural Engineering, 2008)
The equilibrium moisture contents were determined for un-osmosed and pre-osmosed (salt osmosed and sugar osmosed) whole pricked aonla fruit using the static method at 25, 40, 50, 60 and 70degree C over a range of relative humidities from 20 to 90%. The sorption capacity of aonla decreased with an increase in temperature at constant water activity. The sorption isotherms exhibited the phenomenon of hysteresis, in which the equilibrium moisture content was higher at a particular equilibrium relative humidity for desorption curve than for adsorption. The hysteresis effect was more pertinent for un-osmosed and salt osmosed samples in comparison to sugar osmosed samples. The goodness of fit for three parameter sorption models to experimental data was determined. Four models namely the modified Chung Pfost, modified Halsey, modified Henderson and modified Exponential, were evaluated to determine the best fit for the experimental data. For both adsorption and desorption process of aonla fruit, the equilibrium moisture content of un-osmosed and salt osmosed aonla samples can be predicted well by modified Exponential model whereas, modified Halsey model showed good predictive accuracy for sugar osmosed aonla samples.